SCIENTIFIC-METHODOLOGICAL APPROACH FOR PROCESSING HYDROGEOLOGICAL INFORMATION USING GIS TECHNOLOGY (EXAMPLE CHEMICAL COMPOSITION OF GROUNDWATER SOUTHWESTERN PART OF ZAKARPATTIA REGION) - Оstroukh, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of development and testing process flowsheet data processing chemical composition of groundwater alluvial deposits of the southwestern part of the Transcarpathian region based on current GIS software to analyze their spatial and temporal changes.